The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1124/jpet.300.2.655
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Class of Endotoxin Receptor Agonists with Simplified Structure, Toll-Like Receptor 4-Dependent Immunostimulatory Action, and Adjuvant Activity

Abstract: A series of novel, synthetic compounds containing lipids linked to a phosphate-containing acyclic backbone are shown to have similar biological properties to lipopolysaccharide (LPS). These compounds showed intrinsic agonistic properties when tested for their ability to stimulate tumor necrosis factor-␣ in human whole blood and interleukin-6 in U373 human glioblastoma cells without added LPS coreceptor CD14. The presence of the LPS antagonist E5564 completely blocked responses, suggesting that the novel compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 30 publications
0
30
0
1
Order By: Relevance
“…22,23,47,48 Eritoran, a second generation analogue of the lipid A component of LPS, prevented the loss of vascular contractility and led to normal vascular contractions after phenylephrine administration ( Figure 3F). Baumgarten et al have demonstrated that the use of Eritoran is beneficial to maintain cardiac function and myocyte contractility during endotoxemia.…”
Section: Discussionmentioning
confidence: 99%
“…22,23,47,48 Eritoran, a second generation analogue of the lipid A component of LPS, prevented the loss of vascular contractility and led to normal vascular contractions after phenylephrine administration ( Figure 3F). Baumgarten et al have demonstrated that the use of Eritoran is beneficial to maintain cardiac function and myocyte contractility during endotoxemia.…”
Section: Discussionmentioning
confidence: 99%
“…For example, synthetic tetra-acylated lipid A (lipid IVa) is an antagonist of LPS activation of human macrophages (9,21) and penta-acylated LPS extracted from Porphyromonas gingivalis containing extended and branched fatty acyl chains has attenuated activity (26). Hawkins et al (11), using synthetic simplified lipid A-like structures, showed that isomers with R,R,R,R-acyl chain configuration were strongly agonistic, whereas similar compounds with R,S,S,R-acyl chain configuration were much weaker in biologic activity.…”
Section: Vol 72 2004mentioning
confidence: 99%
“…MPL has recently been licensed for use as a vaccine adjuvant (Casella and Mitchell, 2008). TLR4 agonists were also generated during the chemical synthetic program to make E5531 and E5564; some of these compounds, such as E6020 , have good adjuvant activity (Hawkins et al, 2002). Another class of compounds, the aminoalkyl glucosaminide phosphates (AGP), have been developed as immunomodulators that activate TLR4 (Stöver et al, 2004).…”
Section: Pharmacological Manipulation Of Myeloid Differentiation Fmentioning
confidence: 99%